Distinção de sementes, frutos e plântulas das três espécies do genêro Carapa aubl. na Amazônia Central - Gama, Itamara Gonçalves da (Instituto Nacional Pesquisas da Amazônia - INPA, 2019)
In the Brazilian Amazon region occur three species of Carapa. All are popularly known as andiroba and are generally not differentiated when used. The trees are of multipurpose, exploited due to their wood and mainly the oil extracted from the seeds. The present study looked for distinctive characters of these species. This dissertation has two chapters. The first deals with leaf morphology from early development to juvenile plants in comparison with adult plants. In the second chapter, morphobiometric data on fruits and seeds were registered, digital seed images were analysed with Groundeye®, and compared physico-chemical characteristics of seed oil and the calorimetry of the seed reserves. Seeds of three species were collected in the Brazilian states of Amazonas and Pará. From each species data on 18 plants and 115 seeds were collected. Descriptive statistic was used for morphological data and when possible, an analysis of variance (ANOVA) and Tukey test for comparison of means (5% probability). In Chapter 1, the development of seedlings was assessed until the 25th leaf node, the development of cataphylls or leaves, the length of the internodes and total plant height were registered. All three species had a cataphyll at the first leaf node. There was no pattern in the sequence of cataphylls and leaves with an expanded blade along the 25 nodes, neither within the species nor between the species. Until the 5th leaf node, the internodes were longer than afterwards, in all three species. It is possible to distinguish the species by the morphology of the first cataphylls. With further development cataphylls turn similar. Leaflets and the number of leaflets per leaf have distinct characteristics in seedlings and adults and are helpful to distinguish the species. In Chapter 2, the biometric data of fruits and seeds overlapped between C. guianensis and C. surinamensis. However, all biometric variables of C. vasquezii differed from the other two species. The length and width of the seed hilum were useful to differentiate the three species. It was also possible to distinguish the seeds by images of the textures captured with GroundEye®. Seed water content of freshly dispersed seeds was significant higher in C. vasquezii, and consequentely oil extraction based on fresh weight is reduced. Evaluating seed dry mass, the amount of calories was lower in C. vasquezii, which may indicate a different chemical composition. For further studies, we recommend a comparative and more detailed analysis of the seed oils of the three species. In a first evaluation, C. surinamensis seeds have the most favourable set of characteristics (oil content, iodine, saponification) for extraction and use of the oil. Keywords: leaf morphology, biometrics, GroundEye®, oil, calorimetry and water content.
Keywords: Frutos e sementes; Carapa Aubl.